The Effect of Health Literacy Program for Uncontrolled Type 2 Diabetes Mellitus Patients - Klarob, Rattanaporn; Sikaow , Orapin; Prasertsong, Chadapa (Journal of The Royal Thai Army Nurses, 2021)
This quasi-experimental research was to study the effect of health literacy program on health literacy, health behaviors and hemoglobin A1c among uncontrolled type 2 diabetes mellitus patients. The purposive sampling was used, which the samples were diabetes patients. They were then paired into a experimental group and a control group of 31 people each. The research instruments were the health literacy program, which had content validity at 1.00. The health literacy assessment and health behaviors instrument had reliability at 0.84 and 0.80, respectively. Whereas, hemoglobin A1c had been tested. Data were analyzed by using frequency, percentage, mean, standard deviation, pair t-test and independent t-test. The results showed that the majority of the sample were female, which was 62.90 percent. Average age was 48.59 years, secondary education was 41.93 percent. Approximately 82.30 percent had received the knowledge of diabetes. After the experiment, the experimental group had mean score of health literacy and health behaviors at 53.65 and 41.42 respectively which had higher than before the experiment at 38.77 and 30.00 respectively. The experimental group had mean score of health literacy and health behaviors at 53.65 and 41.42 respectively which had higher than the control group at 38.51 and 32.16 respectively. The experimental group had lower hemoglobin A1c (8.21) than the control group (9.69), which was a statistically significant at the .01 level. Suggestion, this health literacy program could reduce blood sugar level of type 2 diabetes mellitus patients.